Implementasi Artificial Intelligence (AI) Dalam Proses Perubahan Konstitusi dan Implikasinya - Darmawan, Abqary Faraz; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Developments over time continue to occur and the constitution itself often evolves with the times, so it is necessary to draft a